Effect of amaranth proteins on the RAS system: In vitro, in vivo and ex vivo assays - Suárez, Santiago (2020)
The aim of this work was to analyse the hypotensive effect of amaranthprotein/peptides on spontaneously hypertensive rats (SHR). The mechanism of action of these peptides was studied in vivo and ex vivo. We also tested the effect of protection against gastrointestinal digestion (GID) exerted by an O:W emulsion on the integrity of the antihypertensive peptides. All samples tested produced a decrease in blood pressure (SBP). The animals treated with emulsion (GE) and emulsion+peptide (GE+VIKP) showed the most significant reduction in the SBP (42±2 mmHg and 35±2 mmHg, respectively). The results presented suggest that after GID, a variety of peptides with biological activities were released or were resistant to this process. These peptides play a role in the regulation of the SBP by acting on plasma ACE, plasma renin and the vascular system. These results support the use of amaranth protein/peptides in the elaboration of functional foods for hypertensive individuals.